Some recent bird observations from Halmahera - Frank Lambert; Dennis Young (Indonesian Ornithologists’ Union, 1989)
During July 1987, the authors spent 10 days on Halmahera, observing birds in the vicinity of Domato (0 deg 53'N, 127 deg 28'E). Most observations were made 6-10 km inland, in the area known locally as